Facebook and the Final Practicum: The Impact of Online Peer Support in the Assistant Teacher Program - Paris, Lisa; Morris, J.; Boston, J. (Edith Cowan University, 2015)
Australian pre-service teachers (PST) frequently report feeling isolated and vulnerable during the high stakes Assistant Teacher Program (ATP) final practicum. Mentoring and online learning communities have been shown to offer effective support during periods in which pre-service and beginning teachers feel challenged. As social media progressively infiltrates all aspects of contemporary life, individuals and organisations are opting to use technology in highly adaptive ways; as a result, they have to navigate both the positive aspects and pitfalls of the medium. In this paper we examine whether university Facebook© support groups, coupled with professional standards training and moderator involvement by university staff, enhanced ATP outcomes for pre-service teachers in art and science.